2007
DOI: 10.1080/09640560701402075
|View full text |Cite
|
Sign up to set email alerts
|

Many ways to say ‘no’, different ways to say ‘yes’: Applying Q-Methodology to understand public acceptance of wind farm proposals

Abstract: This paper explores the nature of public acceptance of wind farms by investigating the discourses of support and objection to a proposed offshore scheme. It reviews research into opposition to wind farms, noting previous criticisms that this has tended to provide descriptive rather than explanatory insights and as a result, has not effectively informed the policy debate. One explanation is that much of this research has been conceived within a positivist research frame, which is inadequate in dealing with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
255
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(262 citation statements)
references
References 70 publications
5
255
0
2
Order By: Relevance
“…European researchers such as Aitken (2010), Ellis (2007), and Taebi (2016) have criticized researchers who portray wind energy opponents as "deviant" and seek to understand opposition merely to "overcome" it, but this criticism of positivist research has not been highlighted or examined to the same degree by North American researchers. It has been suggested that instead of focusing on the reasons for negativity toward wind energy, some researchers have sought methods to ensure approval (Taebi, 2016).…”
Section: Limitations Of Previous North American Wind Acceptance Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…European researchers such as Aitken (2010), Ellis (2007), and Taebi (2016) have criticized researchers who portray wind energy opponents as "deviant" and seek to understand opposition merely to "overcome" it, but this criticism of positivist research has not been highlighted or examined to the same degree by North American researchers. It has been suggested that instead of focusing on the reasons for negativity toward wind energy, some researchers have sought methods to ensure approval (Taebi, 2016).…”
Section: Limitations Of Previous North American Wind Acceptance Researchmentioning
confidence: 99%
“…Another problem with the literature is positivist language toward wind energy, which some researchers have argued may reduce the quality and reliability of research and may prevent meaningful understandings of public acceptance (Aitken, 2010;Ellis et al, 2007). European researchers such as Aitken (2010), Ellis (2007), and Taebi (2016) have criticized researchers who portray wind energy opponents as "deviant" and seek to understand opposition merely to "overcome" it, but this criticism of positivist research has not been highlighted or examined to the same degree by North American researchers.…”
Section: Limitations Of Previous North American Wind Acceptance Researchmentioning
confidence: 99%
“…This is the experience onshore, but as long as wind power is nearshore and still visible from the shore, it can be expected that landscape is still essential (Bishop and Miller, 2007;Ladenburg, 2008). The possibility to achieve a positive fit between local landscapes and wind turbines may be very subjective indeed (Lothian, 1999), but nevertheless the issue of the perceived fit of turbines to the landscape at the site is by far the most important factor in the contrasts between views on wind power implementation (Ellis et al, 2007;Breukers and Wolsink, 2007b). The idea that acceptability offshore will be greater and easier also includes the assumption that offshore wind power schemes would avoid the issue of destroying the landscape (Danielson, 1995).…”
Section: Acceptance Offshorementioning
confidence: 99%
“…Q-Method was first devised in 1935 by William Stephenson, a British psychologist (Brown, 1996). It was originally developed for the scientific study of subjectivity (McKeown and Thomas, 1988), as a means of revealing the subjectivity involved in any given situation (Brown, 1996;Ellis et al, 2007). Its advantages over other methods are that it combines the strengths of both qualitative and quantitative research methods by providing insights into attitudes while providing statistical rigour (Addams and Proops, 2000;Brown, 1996;Webler et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Its advantages over other methods are that it combines the strengths of both qualitative and quantitative research methods by providing insights into attitudes while providing statistical rigour (Addams and Proops, 2000;Brown, 1996;Webler et al, 2009). Q-Methodology benefits are that it is replicable and provides empirical rigour while being participant driven (Ellis et al, 2007;Frantzi et al, 2009;Guimaraes, 2009), in addition to which it 'involves a statistical multivariate analysis of opinions with minimal researcher's bias' (Visser et al, 2007). Yet, despite being a very valued tool in the analysis of stakeholder opinion, Q-methodology has its limitations.…”
Section: Methodsmentioning
confidence: 99%